2007
DOI: 10.1016/s1607-551x(09)70400-0
|View full text |Cite
|
Sign up to set email alerts
|

Splenic Flexure Colonic Volvulus: A Pediatric Case Report

Abstract: Volvulus of the colon is an unusual cause of intestinal obstruction in the pediatric population. Splenic flexure colonic volvulus is the most uncommon site in children. We report a case of splenic flexure volvulus (SFV) in a 21-month-old boy with underlying cerebral palsy and epilepsy. He experienced abdominal distension, bilious vomiting and absence of bowel movement for 2 days. Abdominal radiography showed a proximal distended colon and a "coffee bean sign" at the left upper quadrant. Barium enema revealed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 15 publications
0
10
1
Order By: Relevance
“… 2 6 Mortality from TCV is estimated between 14 and 29%. 4 7 The viable transverse colon after detorsion in this patient differs from many of cases reported where acute fulminant bowel necrosis and gangrene is found at laparotomy. In view of the viable bowel after detorsion and lack of any significant previous gastrointestinal history, acute resection was not necessary.…”
Section: Discussioncontrasting
confidence: 51%
“… 2 6 Mortality from TCV is estimated between 14 and 29%. 4 7 The viable transverse colon after detorsion in this patient differs from many of cases reported where acute fulminant bowel necrosis and gangrene is found at laparotomy. In view of the viable bowel after detorsion and lack of any significant previous gastrointestinal history, acute resection was not necessary.…”
Section: Discussioncontrasting
confidence: 51%
“…For splenic flexure volvulus to occur, these anatomical attachments are congenitally absent or postnatally altered owing to an abdominal operation. Volvulus of the splenic flexure accounts for less than 2% of all cases of colonic volvulus, and there have been 43 cases reported to date with only 7, including our patient, recorded in children [5][6][7].…”
Section: Discussionmentioning
confidence: 71%
“…Surgery is the optimal treatment of splenic flexure volvulus, with the options of simple detorsion, resection of the redundant bowel, or colopexy of the splenic flexure. Simple derotation is discouraged because of a high recurrence rate (32%) similar to endoscopic detorsion [5]. Surgical resection is the most reliable procedure for preventing recurrence, and when the involved segment develops gangrene, resection is essential.…”
Section: Discussionmentioning
confidence: 99%
“…Viable bowel can potentially be detorted and fixed, but previous studies have shown a high rate of mortality and complications with simple detorsion. Primary anastomosis or creation of a stoma should be dictated by patient-related factors, the feasibility of anastomosis, and concern for risks of an anastomosis versus a stoma [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Typically, volvulus occurs in the sigmoid colon or caecum. However, it can occur in any part of the colon where the colon is mobile and not fixed to the retroperitoneum, or the mesentery is elongated [ 1 ]. Splenic flexure volvulus (SFV) is a rare condition of colonic obstruction and is the least common site of the colon to develop volvulus, comprising 2% of colonic volvulus [ 2 ].…”
Section: Introductionmentioning
confidence: 99%